STRATEGIES AND POLICIES IN ENFORCEMENT OF SECURITY, HUMAN RIGHTS AND DEVELOPMENT IN PAPUA - Syamsir, Rudy; Rohman, Syaiful (Journal of Terrorism Studies, 2022)
Papua always an interesting discussion along with the rampant acts of violence against civilians carried out by the Independent Papua Organization (OPM), which were later labeled with various terms such as the Armed Separatist Group (KSB), Armed Criminal Group (KKB), Armed Separatist Criminal Group (KKSB). KKB carried out acts of violence in killing civilians, government officials vandalizing and burning public facilities. Because of the ways that are similar to acts of terrorism, this group is finally called the Armed Terrorism Group (KTB). The Indonesian National Army (TNI) and Indonesian Republic Police (POLRI) security forces have taken repressive actions with armed contact as an effort to uphold law and sovereignty, especially in responding to the actions of armed separatist groups. Although some believe that the crackdown by the officers will lead to human rights violations. In this paper, the author will try to analyze the security enforcement of KTB and also look at the development side of Papua. This study uses qualitative methods with comprehensive analysis through accountable data. Research suggests that the State must provide a sense of security to Papuans who are often terrorized, protect the rights of Papuans who are often taken away by the KTB group. So, it can be said that the repressive actions of the TNI-Polri security forces against KTB were not human rights violations.